The Influence Company Size, Profitability and KAP Size on Audit Delay in Property and Real Estate Sector Companies Listed on The IDX in 2018-2021 - WAHYUNI, Dwi Tasya Indah (PT Keberlanjutan Strategis Indonesia, 2022)
Financial statements are defined as records containing information relating to the financial condition of a company in an accounting period which can bring various benefits to a number of partiesi whoi havei ani interesti in making economic decisions. One of the responsibilities that have been placed on firms that have been listed on the Indonesia Stock Exchange as a kind of corporate management responsibility to the company's external stakeholders is the timely submission of financial reports. Both internal and external factors may have an impact on how accurately the financial statements of the organization are presented. Therefore, the purpose of this study is to ascertain how the firm size, profitability, and KAP size affect audit delay in companies in the property and real estate industry listed on the Indonesia Stock Exchange between 2018 and 2021. Using the purposive sampling technique, a sample of 35 companies is acquired annually, for a total sample of 140 during the course of the four-year study. The secondary data used in this study comes from firm financial statements, which will subsequently be subjected to multiple linear regression analysis. using a computer application, specifically IBM SPSS Version 26. According to the study's findings, firm size and KAP size have no statistically significant effects on audit time, whereas the profitability variable has a significant negative impact.